Dust storm attenuation modeling based on measurements in Sudan - Elsheikh, Elfatih A A; Islam, Md Rafiqul; Habaebi, Mohamed Hadi; Ismail, Ahmad Fadzil; Zyoud, Alhareth (Institute of Electrical and Electronics Engineers Inc., 2017)
Microwave (MW) and millimeter-wave (MMW) propagation are severely affected by dust storms and sand storms in arid and semi-arid areas. Electromagnetic waves may suffer from attenuation due to suspended particles during a dust storm. This paper proposes an empirical model to predict the attenuation due to dust storms based on a one-year measurement of visibility, humidity and their effects on microwave links in Sudan. Signal strength variations on two operational microwave links at 14 GHz and 22 GHz as well as visibility were monitored simultaneously. The model is developed empirically using measured attenuation and measured storm characteristics (e.g., visibility, dielectric constant, frequency and moisture content). The predicted attenuation from the proposed empirical model is compared with the attenuation at frequencies ranging from 7.5 GHz to 40 GHz measured at different locations, and good agreement is found. Additionally, this method is characterized by simplicity and capability to predict reliable dust storm attenuation for a wide range of frequencies and moisture levels.